Is the Antimicrobial Activity of Hydrolates Lower than That of Essential Oils? - Maura Di Vito; Antonina Smolka; Maria Rita Proto; Lorenzo Barbanti; Fabrizio Gelmini; Edoardo Napoli; Maria Grazia Bellardi; Paola Mattarelli; Giangiacomo Beretta; Maurizio Sanguinetti; Francesca Bugli (MDPI AG, 2021)
Among the top five human infections requiring medical treatment is dermatitis. Treatment of bacterial and fungal skin infections is usually based on antibiotic therapy, which is often ineffective due to the involvement of antibiotic-resistant microbial strains. The aim of this study was to compare the antimicrobial activity of essential oils (EOs) and hydrolates (Hys) extracted from six aromatic plants grown in Italy (Lavandula angustifolia, Lavandula intermedia, Origanum hirtum, Satureja montana, Monarda didyma, and Monarda fistulosa) towards fungal (Candida albicans, Candida parapsilosis, Candida glabrata and Candida tropicalis; Trichophyton soudanense, Trichophyton tonsurans, Trichophyton rubrum, Trichophyton violaceum and Microsporum canis) and bacterial strains (Staphylococcus aureus MRSA, Staphylococcus aureus MSSA, Streptococcus pyogenes, E. faecalis, Enterococcus faecalis VRE, and Enterococcus faecium) potentially pathogenic for human skin. The composition and antimicrobial activity of EOs and Hys were evaluated using the Gas-chromatography mass spectrometry and micro dilution-broth test, respectively. The volatiles' conversion factors (CFs) were calculated to compare the activity of Hys with that of the corresponding EOs. Data show that, although the minimum inhibitory concentration values of EOs are lower than the corresponding Hys, the volatiles contained in Hys are more effective at inhibiting microbial growth because they are active at lower concentrations.